Analysing influential factors in e-learning technology acceptance for digital learning effectiveness enhancement - Sahusilawane, Wildoms; Hiariey, Lilian Sarah; Hiariey, Arlene Henny (Journal of Education and Learning (EduLearn), 2024)
This study aims to discover the factors that influence the acceptance of electronic learning media and its effect on the effectiveness of digital instruction. The study involved a learning management system and online tutorials using management system (MS) teams from various faculties at the Universitas Terbuka. These include the Faculty of Economics and Business, the Faculty of Teacher Training and Education, the Faculty of Science and Technology, and the Faculty of Law, Social Sciences, and Political Sciences. also conducted in three regional offices in Ambon, Gorontalo and Makassar, which were selected through purposive sampling. Primary data sources include participant questionnaires and interviews. Analytical methods include correlation and multiple regression analysis, with descriptive statistics used to summarize the dataset. Variable selection involves reliability and validity tests and classical assumption tests like multicollinearity. The F-test demonstrates a statistically significant and beneficial influence of utilizing e-learning media and individual ability, training, and intention to use it for digital learning success. The results of ttests and regression models provide empirical evidence supporting the significant effect of e-learning media and intention to use on the effectiveness of digital learning. However, variables related to training and ability do not show any significant influence.